Effects of Science Achievement Tests, Technology Achievement Tests, Integrated Science, Technology And Community Tests And Micro Practice on Teacher's Entry Level Abilities - Paulo Nyereugo Kwuanyanwu (International Journal of Science and Society, 2019)
This study included both guidance tools and learning cases that were used to explore the entry potential of newly graduated science and technology teachers (NQSTTs). Using a semi-experimental model, the study took 106 NQSTTs, an experimental group (N = 54) and a control group (N = 52), which were subjected to a three-month Professional Certification (PQE) test program. Instruments such as the Science Performance Test (SAT), the Technology Performance Test (TAT), the Integrated Science, Technology and Society Test (ISTST) and microlearning were used to measure the entry capacity of NQSTT. All exams contained versions of the best test and test and were presented to both groups at the start of the study and at the end of the study. Significant changes in the initial ability of the teacher were detected by repeated measurements on ANOVA tests performed for each test with a significance level of 0.05. The results showed that the teachers' initial entry capacity was relatively better than expected, probably due to the type of teacher they were prepared for. It is hoped that these findings will help to show interesting differences in the programs designed to prepare teachers for certification/ admission. The didactic effects on science and technology education are discussed.